Impact of Extra-Intestinal Manifestations at Diagnosis on Disease Outcome in Pediatric- and Elderly-Onset Crohn′s Disease: A French Population-Based Study. Issue 2 (1st August 2018) - Duricova, Dana; Sarter, Hélène; Savoye, Guillaume; Leroyer, Ariane; Pariente, Benjamin; Armengol-Debeir, Laura; Bouguen, Guillaume; Ley, Delphine; Turck, Dominique; Templier, Carole; Buche, Sebastien; Peyrin-Biroulet, Laurent; et al.
Abstract: Background: Extraintestinal manifestations (EIM) have been associated with more severe course of inflammatory bowel disease. The aim was to study the frequency of EIM in pediatric- and elderly-onset Crohn′s disease (CD) and the factors associated with EIM and their impact on long-term disease outcome. Methods: Pediatric- (age at diagnosis younger than 17 years) and elderly-onset CD patients (age at diagnosis 60 years or older) from a prospective population-based registry (EPIMAD) were recruited. Data on EIM and clinical factors at diagnosis and at maximal follow-up were collected. Results: We included 535 pediatric- and 370 elderly-onset patients (median age 14.5 and 69.9 years; median follow-up 11.1 and 5.9 years). Extraintestinal manifestations presented in 23.5% of childhood-onset and 4.9% of elderly-onset individuals at diagnosis, while in 29.8% and 5.9% of patients, EIM developed newly during the follow-up (hazard ration [HR] 4.4, 95% CI, 2.7–7.0, P < 0.001). The most frequently involved organ in both age cohorts, either at diagnosis or during disease course, were joints (pediatric: 11.2% and 22.6%; elderly: 3.2% and 3.5%, respectively) followed by skin (pediatric: 15.9% and 13.6%; elderly: 2.7% and 2.7%, respectively). Extraintestinal manifestations at diagnosis were associated with increased risk for corticosteroids (HR 1.42, 95% CI, 1.14–1.78 and HR 3.38, 95% CI, 1.88–6.08) and immunosuppressive therapy (HR 1.30, 95% CI, 1.02–1.65 and HR 4.24, 95% CI, 1.91–9.42), in both age populations. Conclusions: Extraintestinal manifestations occurred at lower frequency in elderly-onset compared with pediatric-onset patients. In both age populations, presence of EIM at diagnosis independently increased the need for corticosteroid and immunosuppressive treatment.